2022
DOI: 10.1093/cid/ciac586
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Work-related Risk of Coronavirus Disease 2019 (COVID-19): Comparison of COVID-19 Incidence by Occupation and Industry—Wisconsin, September 2020 to May 2021

Abstract: Background Work-related exposures play an important role in SARS-CoV-2 transmission, yet few studies have measured the risk of COVID-19 across occupations and industries. Methods During September 2020 – May 2021, the Wisconsin Department of Health Services collected occupation and industry data as part of routine COVID-19 case investigations. Adults aged 18-64 years with confirmed or probable COVID-19 in Wisconsin were assign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 29 publications
3
13
0
Order By: Relevance
“…Many workers in these occupations and industries must work in close proximity to customers, clients, and coworkers, 53 likely increasing their risk for occupational exposure to SARS‐CoV‐2. These findings are broadly consistent with those of other studies that have found evidence for increased risk of SARS‐CoV‐2 infection among workers in occupation and industry subgroups included in our high‐risk groups 38,43,44,54 …”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Many workers in these occupations and industries must work in close proximity to customers, clients, and coworkers, 53 likely increasing their risk for occupational exposure to SARS‐CoV‐2. These findings are broadly consistent with those of other studies that have found evidence for increased risk of SARS‐CoV‐2 infection among workers in occupation and industry subgroups included in our high‐risk groups 38,43,44,54 …”
Section: Discussionsupporting
confidence: 92%
“…These findings are broadly consistent with those of other studies that have found evidence for increased risk of SARS-CoV-2 infection among workers in occupation and industry subgroups included in our high-risk groups. 38,43,44,54 The overrepresentation of some sociodemographic groups in select occupations and industries is associated with inequities in partially overlaps with the transportation and material moving occupational group, which was not found to have an elevated PMR. Leisure and hospitality industries include accommodation, food services, entertainment, and so forth.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…A higher risk was also found among healthcare workers and other public‐facing worker groups 5,8,10 . Individual states have published data on work‐related incidence of COVID‐19, 11,12 and a national analysis reported seroprevalence of SARS‐CoV‐2 by occupation 13 . To date, only one national assessment of SARS‐CoV‐2 infection prevalence by industry based on self‐report has been completed 5 .…”
Section: Introductionmentioning
confidence: 99%